2004
DOI: 10.1093/annonc/mdh099
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant concurrent radiochemotherapy in locally advanced (IIIA–IIIB) non-small-cell lung cancer: long-term results according to downstaging

Abstract: Neoadjuvant radiochemotherapy is feasible with good pathological DS results. Pathological downstaging was confirmed to have high predictive value. Its use is suggested in the short-term evaluation of induction protocols efficacy in locally advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 32 publications
6
45
1
1
Order By: Relevance
“…These results compare favorably with those of previous trials of trimodality therapy in patients with locally advanced NSCLC, although comparing these results with those of other studies is difficult because of the inclusion of patients with different prognostic factors (8)(9)(10)(11)(12). In all of these studies, the response rates to induction chemoradiotherapy have ranged from 59 to 81%, the complete surgical resection rates have ranged from 45 to 81%, MSTs have ranged from 13 to 25 months, and survival rates at 2 years have ranged from 26 to 66% (8)(9)(10)(11)(12). Additionally, previous studies have reported that downstaging is correlated with rates of survival and distant recurrence (12,18).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…These results compare favorably with those of previous trials of trimodality therapy in patients with locally advanced NSCLC, although comparing these results with those of other studies is difficult because of the inclusion of patients with different prognostic factors (8)(9)(10)(11)(12). In all of these studies, the response rates to induction chemoradiotherapy have ranged from 59 to 81%, the complete surgical resection rates have ranged from 45 to 81%, MSTs have ranged from 13 to 25 months, and survival rates at 2 years have ranged from 26 to 66% (8)(9)(10)(11)(12). Additionally, previous studies have reported that downstaging is correlated with rates of survival and distant recurrence (12,18).…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, previous studies have reported that downstaging is correlated with rates of survival and distant recurrence (12,18). In previous studies, the rate of downstaging has ranged from 12 to 33% (12,13). In the present study, the rate of downstaging was 39.1% among all patients and 64.3% among patients undergoing thoracotomy.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations